Análisis financiero y su incidencia en la toma de decisiones de la empresa Bugathi Constructores SAC, Chiclayo, 2021-2022 - Vasquez Dextre, Valentina Bringith (2025)
This research analyzes the impact of financial analysis on decision-making at the company Bugathi Constructores SAC, located in Chiclayo, during the years 2021–2022. A quantitative approach, non-experimental design, and longitudinal scope were employed, allowing for the evaluation of variable behavior over different points in time. The main objective is to determine how financial analysis influences business decisions, supported by a thorough literature review from sources such as Scielo, Scopus, academic theses, articles, and previous research. Through the analysis of financial data, it is confirmed that tools such as financial ratios, horizontal analysis, and vertical analysis are essential for understanding the company’s economic situation, allowing for the evaluation of key aspects such as liquidity, profitability, and solvency. The findings show that financial analysis has a significant impact on the management of Bugathi Constructores SAC, as it provides relevant information that facilitates precise and timely decision-making aimed at optimizing resources and achieving strategic goals in the medium and long term